TRPA1 Channel Activation Inhibits Motor Activity in the Mouse Colon - Hassan, Abdul-Azim; Sleet, Ben; Cousins, Zoe; Keating, Chris David (Frontiers in Neuroscience, 2020)
There is a growing awareness of the role that TRP channels play in regulating sensory and motor functions in the gastrointestinal tract. In this study we used an in-vitro murine model of colonic peristaltic-like complexes (CPMCs) to evaluate the role of exogenous and endogenous TRPA1 signalling processes in regulating colonic motility. Using in-vitro recordings of intraluminal pressure to monitor the presence of CPMCs in colonic segments we performed a series of experiments on male CD1 mice (2 months of age) and found that CPMC activity was attenuated by TRPA1 agonists. Bath application of the TRPA1 antagonist HC-030031 had no effect upon basal CPMC activity whereas application of the synthetic TRPA1 agonist ASP7663 caused a reversible dose dependent decrease in CPMC frequency that was blocked by HC-030031. Cinnamaldehyde and 4-hydroxy-2-nonenal elicited long lasting decreases in CPMC frequency that were blocked by HC-030031 whereas the decreased CPMC activity invoked by AITC could not be blocked by HC-030031. Our results show that any potential mechanosensory function of TRPA1 doesn’t involve contributing to distension induced colonic motor activity and that a role for TRPA1 in the colon is through regulating motility through exogenous and endogenous agonist induced inhibitory effects.